Perception of health risk linked to environmental factors by pregnant women. (13th November 2019) - Sauvant-Rochat, M; Kouamé, N G L; Bernard, L; Marie, C; Lémery, D; Vendittelli, F
Abstract: Bacground: Recently, the International Federation of Gyneco-Obstetrics (FIGO) advocates limiting exposure to chemicals present in everyday products during pregnancy. To date, the chemicals, and the risks related, are not well-known, as well by perinatal health professionals (PHP) as by pregnant women (PW). AIMS: to estimate the sensitivity to the environment and the perception of risks related to chemical substances by pregnant women. Methodology: A descriptive cross-over study was carried out among pregnant women ((followed or hospitalized in different health establishments in Auvergne). The collection of data (socio-demographic characteristics, sensitivity to the environment, use of cosmetics, perception of environmental risks) was carried out by interviewers, using a standardized questionnaire. The statistical analysis (logistic regression) was performed with Modalisa® 8.0 (Kynos, Paris). Results: Three hundred questionnaires were analyzed. The sensitivity to the environment is estimated at 6.3 ± 1.7 (scale 0 to 10). For the majority of women, exposure to chemicals is primarily related to the use of cleaning products, DIY products, and gardening products. Food can also be a source of exposure (especially for pesticides). On the other hand, cosmetics are not perceived as products containing chemical substances, with potential risk to health. This vision of chemical substances is related to age, educational level, socio-professional category and sensitivity to the environment. Only 5% (19/300) of PW considered health professionals as referents on chemical substances and environmental problems. Conclusions: This study highlighted the sensitivity of pregnant women to environmental issues, but a lack of knowledge of chemicals and the risks which they represent for health. It is important to reinforce the information given to pregnant women by perinatal health professionals about healthy behaviors. Key messages: Pregnant women don't know all sources of exposure to chemical substances. Training in environmental health must be increased for perinatal health professionals.